2020
DOI: 10.1109/access.2020.2981878
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Power Harvesting and Cyclostationary Spectrum Sensing in Cognitive Radios

Abstract: We expect that 5G will support a large volume of data traffic to provide various services with a low latency. This will inevitably require an increased amount of energy. Wireless power transfer needs a higher receiver sensitivity than data decoding. Increased electromagnetic fields may introduce harmful effects on living organisms. Fortunately, massive multiple-input and multiple-output (MIMO) can provide significant gains in radiated energy and spectral efficiencies. Cognitive radio and 5G are emerging techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Examples are illustrated, which show the method's efficiency in identifying the unknown CFs. The same approach is employed in [93] to provide spectrum sensing-based energy harvesting (EH) which enables the SU to utilize the identified PU signal as a battery charge. Specific expressions for G y (α c ) in the cases of several modern wireless communication signals (such as MSK/PSK/QAM) are derived.…”
Section: ) Spectral Correlation-based Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are illustrated, which show the method's efficiency in identifying the unknown CFs. The same approach is employed in [93] to provide spectrum sensing-based energy harvesting (EH) which enables the SU to utilize the identified PU signal as a battery charge. Specific expressions for G y (α c ) in the cases of several modern wireless communication signals (such as MSK/PSK/QAM) are derived.…”
Section: ) Spectral Correlation-based Detectionmentioning
confidence: 99%
“…Works in this field have diverged into two areas -rigid detection in low SNR, and lower number of computations for the TS. The former direction has yielded notable advancements in detecting the PU signal via TS based on the ACF, CAF or SCD, even in the presence of noise uncertainty and fading [77], [78], [89], [93]. On the other hand, if the pairs (α c , τ ) for which the received signal is tested, are known, lowest complexity is usually achieved by ACF approaches because, in order to compute CAF and SCD, more Fourier transformations are necessary.…”
Section: ) Lessons Learnedmentioning
confidence: 99%
“…In the next simulation, we concentrate on analyzing spectral efficiency and power control in scalable cell-free massive MIMO networks. Moreover, the NFOEnsemble method is compared with the NFOPar2 method and the method of [9]. As shown in Fig.…”
Section: B Simulation Of Cellular Networkmentioning
confidence: 99%
“…In [8], the authors developed a novel transmission scheme by superposing the training symbols for active device detection and channel estimation on the data symbols in the uplink transmission to mitigate the cross interference among the superposed signals and improve the efficiency. In [9], the authors showed that cognitive spectrum sensing and power harvesting can be accomplished simultaneously. They focused on cyclostationary spectrum sensing.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of proposed system can sense both kinds effectively, but the proposed system cannot sense for SNR>(-7) dB. In 2020, Jang [8] have used the CFD for the massive multiple-input and multiple-output (MIMO)-based mmWave-5G network. Though the proposed system is effective for different mappers and low SNR, the CFD requires coherency rather than higher complexity.…”
Section: Introductionmentioning
confidence: 99%